Private Islamic Higher Education in Asean Economic Community (AEC) Era - Mulyawan Safwandy Nugraha; Dadang Sahroni; Aeni Latifah (Jurnal Pendidikan Islam, 2016)
This article explores the challenge faced by Indonesia in ASEAN Economic Community (AEC) era. It is also revealed the Private Islamic Religion Institution (PTKIS) strategic to play its role and function in generating human resource. The method used is qualitative in the form of literature study. The result shows that PTKIS are required to adapt and see the AEC as an opportunity to change. A private status should be used as an institutional capital to create and innovate freely, by maximally utilizing the available resources. The management of a reputable institution is seen to be a significant factor for reinforcement. Aspects of visionary leadership, qualified lecturers, a curriculum that is responsive to a change, and an adequate infrastructure become a strengthening point toward the management accountability of universities in creating graduates who are competitive, skillful and qualified.